Gene expression in atherogenesis - Monajemi, H; Arkenbout, E K; Pannekoek, H (Thrombosis and haemostasis, 2001)
It is conceivable that the extent and spatio-temperal expression of dozens or even a few hundred genes are significantly altered during the development and progression of atherosclerosis as compared to normal circumstances. Differential gene expression in vascular cells and in blood cells, due to gene-gene and gene-environment interactions can be considered the molecular basis for this disease. To comprehend the coherence of the complex genetic response to systemic and local atherosclerotic challenges, one needs accessible high through-put technologies to analyze a panel of differentially expressed genes and to describe the interactions between and among their gene products. Fortunately, new technologies have been developed which allow a complete inventory of differential gene expression, i.e. DD/RT-PCR, SAGE and DNA micro-array. The initial data on the application of these technologies in cardiovascular research are now being reported. This review summarizes a number of key observations. Special attention is paid to a few central transcription factors which are differentially expressed in endothelial cells, smooth muscle cells or monocytes/ macrophages. Recent data on the role of nuclear factor-kappaB (NF-kappaB) and peroxisome proliferation-activating receptors (PPARs) are discussed. Like the PPARs, the NGFI-B subfamily of orphan receptors (TR3, MINOR and NOT) also belongs to the steroid/thryroid hormone receptor superfamily of transcription factors. We report that this subfamily is specifically induced in a sub-population of neointimal smooth muscle cells. Furthermore, intriguing new data implicating the Sp/XKLF family of transcription factors in cell-cell communication and maintenance of the atherogenic phenotype are mentioned. A member of the Sp/XKLF family, the shear stress-regulated lung Krüppel-like factor (LKLF) is speculated to be instrumental for the communication between endothelial cells and smooth muscle cells. Taken together, the expectation is that the fundamental knowledge obtained on atherogenesis and the data that will be acquired during the coming decade with the new, powerful high through-put methodologies will lead to novel modalities to treat patients suffering from cardiovascular disease. In view of the phenotypic changes of vascular and blood-borne cells during atherogenesis, therapeutic interventions likely will focus on reversal of an acquired phenotype by gene therapy approach or by using specific drugs which interfere with aberrant gene expression.